Pendidikan dan Bimbingan Anak Berkebutuhan Khusus (ABK) Disleksia - Darmayanti, Nelfil; Hayati, Nurlailla; Rohali, Alila; Marpaung, Zulham Elfelndil (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of scientific research is to find out the process of learning and learning skills in inclusive schools for students with disabilities and the ability of ABK to receive learning with methods implemented in schools and to find out the teacher's efforts in motivating students with disabilities. Illiterate research uses a qualitative research approach. Scientific research is descriptive research, with detailed descriptions of the results of observations, interviews and documents. The resulting data will be analyzed qualitatively and will be described in descriptive form. The result of the study is the process of learning and teaching skills in teaching and learning activities in inclusive schools for students in the lecturing is still being averaged with other normal children, namely by using the 2013 curriculum, so that ABK is included in the lecturing must be supplemented with additional assignments from the selection teacher who was provided by the school's electives inclusive. Learning from the teacher by repeating letters of the alphabet again, rearranging letter cards into words or sentences, and repeating words in reading is very helpful for flexible children in overcoming reading difficulties. The existence of motivation from the teacher makes students more enthusiastic about the direction and guidance of the teacher. Keywords: Children with Special Needs, Education